Purchasing preferences of mothers/caregivers regarding Sangkap Pinoy Seal (SPS) food products and their preschoolers' micronutrient intake in selected areas of Pasig City - Huelar, Paula C. (Philippine Journal of Nutrition, 2004)
This study aimed to determine the purchasing behavior of mothers/caregivers and their preschoolers' micronutrient intake in selected areas of Pasig City. Personal interview and 24-hour food recall using structured and pretested questionnaires were administered among 205 randomly selected respondents. Data were analyzed descriptively and relationships among variables were established using chi-square tests and t-tests for equality of means. The Statistical Package for Social Sciences (SPSS) and Individual Dietary System (IDES) were utilized for statistical analyses. Data showed that 72.9% Sangkap Pinoy Seal (SPS) food product users knew about the program. Majority (72.7%) of both users and non-users did not consider the seal when purchasing fortified food products. The fortifide food products consumed were instant mami noodles, snack food, other cereal products, meat and fish products, milk and milk products,chocolate drinks, fats and oils, fruit juices and condiments. Among those that were consumed daily are instant mami noodles, fruit juices, condiments, meat and fish products, fats and oils. Purchases were made from grocery stores, supermarkets or sari-sari stores. Iodized salt was purchased from the health centers. Fortified food products were purchased because they are nutritious and the favorites among the household members. Television and food labels were the sources of information about the seal. Higher mean intakes of protein, vitamin A, iron, iodine, fats, carbohydrates and energy were observed among users of SPS food products. Significant differences between the users and non-users were observed only in age, educational attainment, energy and carbohydrate intakes but not in household size, income, occupation and intakes of protein, vitamin A, iron, iodine and fat. Purchasing and consuming SPS food products helped increase their nutrient intakes. The study advanced several recommendations namely, (1) complementing food fortification with nutrition education/ counselling, (2) incorporating food fortification and reading food labels in the school curriculum, (3) providing incentives to food producers of SPS food products to maintain competitive pricing, and (4) tapping television and movie personalities to promote fortified food products. Follow up studies may also be done in three ecological settings, e.g. urban, fishing and framing villages to include biochemical assessment and market surveys of SPS Food products.